2015
DOI: 10.1590/0103-8478cr20141227
|View full text |Cite
|
Sign up to set email alerts
|

Beef heifers grazing behavior and herbage intake in natural grassland under rotational grazing

Abstract: It was evaluated the effect of two rest intervals between grazing occupations in rotational grazing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
4
2
2
3
Order By: Relevance
“…According to Carvalho and Moraes (2005), in swards with non-limiting herbage allowance, animals present a higher number of meals promptly filling their rumen in less time. Our results confirm this assertion; the meal duration (min per meal) was shorter than results previously found by other authors working with a similar grassland composition (Barbieri et al, 2015;Mezzalira et al, 2012). These authors found an average of 118 minutes in similar herbage allowance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to Carvalho and Moraes (2005), in swards with non-limiting herbage allowance, animals present a higher number of meals promptly filling their rumen in less time. Our results confirm this assertion; the meal duration (min per meal) was shorter than results previously found by other authors working with a similar grassland composition (Barbieri et al, 2015;Mezzalira et al, 2012). These authors found an average of 118 minutes in similar herbage allowance.…”
Section: Discussionsupporting
confidence: 91%
“…The bites rate, feeding time (feeds per min), and steps between feed stations were similar to results reported by Barbieri et al (2015), that found on average 35, 6.0 and 2.9 respectively. The average sward conditions that promoted a high daily forage intake, as well as an increased nutrient intake rate, by cattle grazing natural grassland of the Pampa Biome occurred around 12.1% BW of forage allowance, characterized by biomass between 1 820 and 2 280 kg DM ha -1 and between 11.5 and 13.4 cm of height, with tussock levels that did not exceed 30% (Da Trindade et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mean stocking rate was two-fold higher in the present study compared to values reported by FONTOURA JÚNIOR et al (2007);NEVES et al (2009);SOARES et al (2005), and similar to cool season annual pastures (POTTER et al, 2010). Similar stocking rate were achieved by QUADROS et al (2011) andBARBIERI et al (2015) using the same experimental protocol. Therefore, stocking rate of the present study could be regarded as high and could be attributed to high leaf mass, herbage mass and leaf allowance.…”
Section: Discussionsupporting
confidence: 69%
“…Pre-grazing herbage mass was similar among the treatments, unlike data from QUADROS et al (2011) andBARBIERI et al (2015). These authors reported significant differences in the pre-grazing herbage mass amongst treatments using a similar protocol (same thermal accumulation rest intervals) to the present study.…”
Section: Discussioncontrasting
confidence: 67%